Improving Financial Management Literacy: A Community Service about Pre-Marriage Schools for Muslimah using ABCD Approach: Peningkatan Literasi Pengelolaan Keuangan Pra-nikah untuk Muslimah - Amijaya, Rachmania Nurul Fitri; Yasin, Mohammad Zeqi; Erlangga, Okyviandi Putra (Institute for Research and Community Services, 2024)
Planning a wedding's finances is one aspect of the process. Before marriage, most couples were made up of two people with fairly autonomous financial arrangements; but, after a year, some began to adopt a more communal structure. In order to help you become more financially literate and more equipped for marriage, this article will outline community service opportunities. by putting into practice a community service plan at the Multazam Study Club utilizing the ABCD (Asset Based Community Development) approach, which is asset-based and sustainable community development. According to the service article's conclusion, students who perform community service in pre-marital schools gain more money management expertise. Following their attendance at lectures and chat shows on WhatsApp, the participants were able to comprehend the need of financial literacy. Based on the completed financial management course, a large number of individuals are aware of investments, emergency money, zakat, infaq, sadaqah, and waqf. In the meanwhile, participants tended to select their own investments; the majority of them selected gold. Putting together community service projects to enhance financial literacy within the framework of marriage has been successful in raising participants' comprehension and decision-making skills. The long-term financial well-being of people and families may be influenced by ongoing initiatives to advance financial empowerment and education in society.